Use of multifractals to detect Anomalous Propagation (AP) in weather radar - Kasparis, Takis; Charalampidis, Dimitrios; Jones, Linwood W. (My University, 2000)
In this paper we present an automatic algorithm for the removal of echoes that are caused due to anomalous propagation(AP) from the lower radar elevation. The algorithm uses textural information as well as intensity characteristics of reflectivity maps that are obtained from the two lower radar elevations. The texture of the reflectivity maps is analyzed with the help of multifractals. We present examples that illustrate the efficiency of our algorithm. We compare our algorithm with a manual algorithm that was developed by NASA/TRMM for AP removal, in terms of total rain accumulation and in terms of the number of pixels removed.
Keywords: Algorithms; Meteorological satellites; Fractals; Multifractals; Calibration; Echo suppression (Telecommunication)